Simulação realista de redes de sensores sem fio industriais - Queiroz, Diego Véras de (2016)
A Wireless Sensor Network (WSN) can be characterized by the use of sensor nodes in varied environments for many different applications, e.g., monitoring and control systems applications in industrial environments. The use of WSNs in industrial applications must deal with typical problems of wireless networks, such as high attenuation and obstructions. In these environments, different characteristics of the channels can be observed due to its multipath profile. Changes in the topology may also cause changes in the channel characteristics as the time goes on, and it may cause differences in the average value of the received power. An alternative to deal with it and with the variation of channel quality is the development of protocols that use multiple channels. Its use allows, e.g., to achieve better use of the channel, increasing the network transmission capacity. However, there is a difficulty in evaluating and comparing different approaches due to the lack of simulators which have more accurate models. To assess the real benefits of these protocols, one should take into account a more realistic propagation model. This work presents a realistic simulation model that captures the effects of fading on a large and small scale, log-normal shadowing, the non-stationary characteristics of the channel for a long time, and the different characteristics of the different IEEE 802.15.4 standard channels. The model was then built into the open-source discrete event simulator Castalia and tested, comparing it with the default stationary model of the simulator. After integration, the protocol Tree-based Multi-Channel Protocol (TMCP) was evaluated using the proposed model. In the experiments it was possible to identify good accuracy in both the model and the TMCP protocol.